2017
DOI: 10.1093/infdis/jix014
|View full text |Cite
|
Sign up to set email alerts
|

Polio Legacy in Action: Using the Polio Eradication Infrastructure for Measles Elimination in Nigeria—The National Stop Transmission of Polio Program

Abstract: From 2012 to date, Nigeria has been the focus of intensified polio eradication efforts. Large investments made by multiple partner organizations and the federal Ministry of Health to support strategies and resources, including personnel, for increasing vaccination coverage and improved performance monitoring paid off, as the number of wild poliovirus (WPV) cases detected in Nigeria were reduced significantly, from 122 in 2012 to 6 in 2014. No WPV cases were detected in Nigeria in 2015 and as at March 2017, onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…13 Several studies have shown that both programs can support each other in achieving targets. [15][16][17] However, an important argument is that these complementary effects are not automatic; they have to be deliberately planned. 18 Guidance is available for this planning to absorb polio resources into immunization and other public health programs during post-polio times.…”
Section: Discussionmentioning
confidence: 99%
“…13 Several studies have shown that both programs can support each other in achieving targets. [15][16][17] However, an important argument is that these complementary effects are not automatic; they have to be deliberately planned. 18 Guidance is available for this planning to absorb polio resources into immunization and other public health programs during post-polio times.…”
Section: Discussionmentioning
confidence: 99%
“…An indirect financial advantage is that the organizational capabilities experience expertise and facilities including laboratories in the Global Polio Laboratory Network may be employed to solve other health-related problems (for example, in Nigeria, some staff in the Centers for Disease Control and Prevention will use their technical experience with polio to improve measles surveillance, routine measles vaccination coverage, and measles outbreak investigation and response in high-risk areas [371]).…”
Section: Future Directions: the Endgame Stage Of Eradication And Sustmentioning
confidence: 99%
“…The engagement of community leaders was generated by local-based staff of the National Stop Transmission of Polio (NSTOP) program, which was established in 2012 to create a network of staff working at national, state, and district levels in areas deemed high risk for vaccine-preventable disease outbreaks [17]. Town announcers promoted the micro-census across the ward during the two days preceding the activity and throughout the enumeration period, 11-17 July, 2018.…”
Section: Enumeration Proceduresmentioning
confidence: 99%